Experimental Study on Dewatering of Hydraulic Silts by Horizontal Electroosmosis Combined with Surcharge Preloading - YANG Yang; CHEN Renyuan; QIU Zhenfeng; WU Liqing (Renmin Zhujiang)
A large amount of dredging silt will be produced in the urban water environment treatment project.With high water content and large volume,the silt will occupy a lot of land resources after being dumped in the storage yard directly.This paper designs a model test for the treatment of hydraulic silts by the horizontal electroosmosis method,performs the dewatering of hydraulic silts through the horizontal electroosmosis combined with surcharge preloading,verifies the feasibility and advantages of horizontal electroosmosis for silt dewatering.The test results show that:The upper load can limit the crack width of silt.The larger the upper load is,the smaller the crack width of silt is,the bigger the silt settlement is,the larger the silt displacement is,and the lower the moisture content is.The upper load can delay the attenuation of electric flow and the reduction of the effective electric potential,which is conducive to the dewatering and consolidation of silt.At the final stage of electroosmosis,the energy consumption is high and the dewatering is small.Therefore,in practical application,electroosmosis should be stopped before this stage.